A new 3D Cd(II) coordination polymer constructed by mixed-ligand strategy: synthesis, crystal structure and properties. Issue 3 (4th March 2021) - Wang, Yu-Fang; Zhang, Yong-Hua
Abstract: A new 3D Cd(II) coordination polymer, {[Cd2 (btc)(HL)(H2 O)]·3H2 O} n (1 ) (H2 L= 3-(1H-pyrazol-4-yl)-5-(pyridin-2-yl)-1, 2, 4-triazole; H3 btc = 1, 3, 5-benzenetricarboxylic acid), has been synthesized by hydrothermal reaction of Cd(NO3 )2 ·4H2 O, H2 L and H3 btc. It has been structurally characterized by element analysis, IR. X-ray single-crystal analysis was carried out for 1, which crystallizes in the monoclinic system, space group P21 / n . The single X-ray diffraction reveals that compound 1 exhibits 3D framework structure. The luminescence properties of H2 L and compound 1 were investigated at room temperature in the solid state. Furthermore, the thermal decomposition behavior of the compound is characterized by thermogravimetric analyses.